Induction of Protective Immunity against Chlamydia muridarum Intravaginal Infection with a Chlamydial Glycogen Phosphorylase - Li, Zhihong (Public Library of Science, 2012)
We evaluated 7 C. muridarum ORFs for their ability to induce protection against chlamydial infection in a mouse intravaginal infection model. These antigens, although encoded in C. muridarum genome, are transcriptionally regulated by a cryptic plasmid that is known to contribute to C. muridarum pathogenesis. Of the 7 plasmid-regulated ORFs, the chlamydial glycogen phosphorylase or GlgP, when delivered into mice intramuscularly, induced the most pronounced protective immunity against C. muridarum intravaginal infection. The GlgP-immunized mice displayed a significant reduction in vaginal shedding of live organisms on day 14 after infection. The protection correlated well with a robust C. muridarum-specific antibody and a Th1-dominant T cell responses, which significantly reduced the severity but not overall incidence of hydrosalpinx. The GlgP-induced partial protection against upper genital tract pathology suggests that GlgP may be considered a component for a multi-subunit vaccine. These results have demonstrated that intramuscular immunization of mice with purified proteins can be used to identify vaccine antigens for preventing intravaginal infection with C. trachomatis in humans.